Internalisasi Nilai-Nilai Pendidikan Akhlak melalui Konsep Amar Ma'ruf Nahi Munkar: Telaah Kitab Tanbihul Ghafilin Karya Abu Laits As-Samarqandi - Munawaroh, Avita Rohmatul; Hidayati, Eka Wahyu (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
In the increasingly innovative digital age, moral deviations are rife in society. This study aims to explore the values of moral education in the concept of 'amar ma'ruf nahi munkar' as presented in the book Tanbighul Ghafilin and to describe the implementation of these values in the concept of 'amar ma'ruf nahi munkar' according to the book Tanbighul Ghafilin. This research employs a qualitative approach, utilizing a library study to collect research materials from books, journals, magazines, and other documents. The primary data source for this research is the Tanb?h Al-G?fil?n book by Al-Faqih Abu Laits As-Samarqandi, and secondary data related to the research theme. The analysis uses content analysis. The results of the study show that the values formed are sincerity, repentance, silaturrahmi, hasud, Arrogance, guarding the tongue, greed, patience, gratitude, shame. How to implement the values of moral education with the concept of amar ma'rf nahi munkar, such as Ikhlas: believing that charity is from Allah, Taubat: Being able to control one's tongue, Silaturrahmi: giving to each other, Hasud/ Envy/ Jealousy: eliminating destructive prejudices, Arrogance: having a sense of humility, Guarding the tongue: holding back emotions, Patience: controlling emotions, Gratitude: saying thank you and being open-minded, Shame: to fellow human beings and Shame to Allah. This research demonstrates that the values of moral education reflect all commendable values, and implementing them involves consistently positioning oneself as a pious servant of Allah.